The Discipline of Information Studies in Nigerian Universities: Proposal for Unbundling Viable Independent Academic Programmes for the Knowledge Economy - Igwe, Kingsley N. (Communicate: Journal of Library and Information Science, 2024)
The need to advance the education and training of librarians, information professionals, and knowledge managers in the era of the knowledge economy, the fourth industrial revolution (4IR) and the emerging fifth industrial revolution (5IR) is the justification for this article. With variations in nomenclature across the universe like library and information science (LIS), information studies, information science, information management, information and knowledge management, and now knowledge science, the fact in Nigeria remains that education and training targeted at producing core and market-ready information professionals in the afore-stated areas is in endangered position. The perceived abandonment of the 2020 report of the Nigerian Association of LIS Educators (NALISE) curriculum committee and the uncoordinated balkanization of information management programmes as seen in the Core Curriculum and Minimum Academic Standards (CCMAS) by the National Universities Commission (NUC) led to this scholarly piece that developed curriculum for bachelor of science degrees in viable independent academic programmes (LIS; Archives, Records and Information Management; Knowledge Management; Publishing and Digital Technology) that would fit into the proposed discipline/faculty of information studies in Nigerian universities. It is expected that this curriculum development will spur thoughts and perspectives, and possibly serve as a roadmap that will drive and facilitate the actualization of a discipline/faculty of information studies in Nigerian universities.